Perceptions about Consumer Protection Laws and the Consumer Forum: An Emperical Study of Complainant-Consumers of Gulbarga District - Tangade, Shrimant F.; Basavaraj, C.S. (Indian Journal of Marketing, 2006)
There are number of laws, concerning the protection of consumers, framed by the Government from time to time. Also, to see that justice is provided to the consumers Government has set up Consumer Forums in all the districts. These Forums admit consumer complaints and proceedings are carried out on the basis of the provisions of the Consumer Protection Act. Since the consumers have every right to be protected against exploitation of different forms, such defence / protection is mainly dependent on their awareness about laws enacted by the Government to protect the consumers. Lack of awareness leads to non-filing of complaints against the traders at proper time and consequently non-redressal of the grievance of consumer.